Pengaruh perbedaan konsentrasi olahan air lindi terhadap kelimpahan Chlorella sp - Rosyadi Rosyadi; Agusnimar Agusnimar; Hisra Melati (Dinamika Lingkungan Indonesia, 2022)
Leachate, as liquid waste is rich in nutrients, can be used as organic material for the microalgae culture such as Chlorella sp. This study aims to determine the effect of different concentrations to of leachate on the abundance of Chlorella sp populations. The observation was conducted at the laboratory of Microalgae, Agriculture faculty, Islamic University of Riau. The method used in this study was an experimental method using a randomized design; one factor, namely the different concentrations of leachate with five levels, were  5%, 10%, 15%, 20%, and 25%/l of water and three replications. The testing organism in this study was phytoplankton Chlorella sp. The culture container used was a gallon with 20 L of capacity and a water volume of 16 L. The measured parameters were cell abundance, specific growth rate, and water quality. The obtained results showed that the highest abundance of Chlorella sp at a concentration of 25% at 7,322,222 cells/ml, and the peak on day 16, the lowest concentration of 5%, was 2,580,556 cells/ml. On the sixth day, the highest specific growth rate was at a concentration 5% at 0.195/day, and the lowest was 20% at 0.077/day.